Implementasi Kegiatan Ekstrakurikuler Keagamaan di MI Islamiyah Banat Jatisari Senori Tuban - Chairuddin, M.; Moh. Yusroni, Moh. Yusroni (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2024)
This study aimed to analyze the implementation of religious extracurricular activities at MI Islamiyah and their impact on forming students' religious character. This study used a descriptive qualitative approach. Data were collected through interviews, participant observation, and documentation from key informants such as the principal, teachers, and students. Data analysis was carried out using the Miles and Huberman model which includes data reduction, presentation, and concluding, and using triangulation for validation. This approach provides an in-depth picture of the planning, implementation, and impact of extracurricular activities on students' character. The results showed that religious extracurricular activities were well planned, implemented, and supported by students, teachers, and parents. The program includes activities such as the art of reading the Qur'an, congregational dhuha prayer, nasyid, and commemorating Islamic holidays. These activities succeeded in forming students' religious habits. The program evaluation assessed student attendance and participation, as well as changes in their attitudes. The evaluation results showed an increase in students' discipline and religious behavior.